The advanced cyclist's training manual : fitness and skills for every rider - Edwardes-Evans, Luke. (London : A. & C. Black, 2010)
Whether riding competitively or for pleasure, this book will help you realise your cycling goals. It covers training through the off-season and explains how to peak at the right time. There is step-by-step guidance on improving technique, endurance and speed, and plenty of advice on important elements like nutrition and avoiding injuries. Highly practical and easy to use, it also comes with ready-made training plans and template training diaries.
Includes index.
Keywords: Cycling -- Training